2005
DOI: 10.1103/physrevb.72.144108
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure Raman study of the ferroelastic rutile-to-CaCl2phase transition inZnF2

Abstract: The high-pressure Raman spectra of ZnF 2 have been measured up to 6.8 GPa and provided unambiguous evidence of a phase transition from its ambient-pressure rutile ͑D 4h 14 ͒ to the CaCl 2 -type orthorhombic ͑D 2h 12 ͒ structure at a pressure P c Ϸ 4.5 GPa. Both macro-and micro-Raman spectra have been independently obtained at high pressures leading to the same conclusion about the high-pressure phase and the P c . The transition appears to be closely associated with the B 1g ͑A g ͒ Raman-active soft mode of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
4
22
0
1
Order By: Relevance
“…The same transition is also observed as a function of temperature in CaBr 2 (Raptis et al, 1989;Raptis and McGreevy, 1991;Hahn and Unruh, 1991;Unruh, 1993;Kennedy and Howard, 2004;Howard et al, 2005), and ferroelastic twins have been observed in this material by optical microscopy at room temperature (Unruh, 1993). It is observed as a function of pressure in a much wider range of materials, including MgF 2 (Haines et al, 2001;Kanchana et al, 2003;Zhang et al, 2008;Kusaba and Kikegawa, 2008b), FeF 2 (Wang et al, 2011), CoF 2 (Wang et al, 2011), NiF 2 (Wang et al, 2011), ZnF 2 (Perakis et al, 2005;Kusaba and Kilegawa, 2008a), TiO 2 (Nagel and OKeeffe, 1971;Fritz, 1974), MnO 2 (Haines et al, 1995), GeO 2 (Haines et al, 1998(Haines et al, , 2000Lodziana et al, 2001;Ono et al, 2002b), RuO 2 (Haines and Leger, 1993;Ono and Mibe, 2011), SnO 2 Parlinski and Kawazoe, 2000;Hellwig et al, 2003), PbO 2 (Haines et al, 1996), and MgH 2 (Zhang et al, 2007).…”
Section: Introductionsupporting
confidence: 49%
“…The same transition is also observed as a function of temperature in CaBr 2 (Raptis et al, 1989;Raptis and McGreevy, 1991;Hahn and Unruh, 1991;Unruh, 1993;Kennedy and Howard, 2004;Howard et al, 2005), and ferroelastic twins have been observed in this material by optical microscopy at room temperature (Unruh, 1993). It is observed as a function of pressure in a much wider range of materials, including MgF 2 (Haines et al, 2001;Kanchana et al, 2003;Zhang et al, 2008;Kusaba and Kikegawa, 2008b), FeF 2 (Wang et al, 2011), CoF 2 (Wang et al, 2011), NiF 2 (Wang et al, 2011), ZnF 2 (Perakis et al, 2005;Kusaba and Kilegawa, 2008a), TiO 2 (Nagel and OKeeffe, 1971;Fritz, 1974), MnO 2 (Haines et al, 1995), GeO 2 (Haines et al, 1998(Haines et al, , 2000Lodziana et al, 2001;Ono et al, 2002b), RuO 2 (Haines and Leger, 1993;Ono and Mibe, 2011), SnO 2 Parlinski and Kawazoe, 2000;Hellwig et al, 2003), PbO 2 (Haines et al, 1996), and MgH 2 (Zhang et al, 2007).…”
Section: Introductionsupporting
confidence: 49%
“…We conclude that more than the ionic radii (stereochemistry basis), d bonding plays an important role in the stabilization of given phases at high pressure. The similitude between the phase-transition sequence exhibited by CoF 2 (3d 7 ) and FeF 2 (3d 6 ) in comparison to ZnF 2 and MgF 2 (closed-shell configurations) underlines the strong influence of an open d-orbital configuration (3d 7 or 3d 6 ) in stabilizing different phases upon compression. The Raman mode frequency and its pressure dependence are close to those obtained from first-principles calculations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Most transformations yield a high variety of energetically equivalent structures, which are characterized by an increase of the TM coordination number upon compression. Due to their simple composition and bonding, the phase-transition sequence shows some common features associated with the coordination polyhedra, providing a general polymorphic description for these transformations, which results in the interest in geophysics as well as in materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical works have been done to investigate the high-pressure phase transition of ZnF 2 [8][9][10]. It was observed that a phase transition from the rutile- type to the CaCl 2 -type structure occurs at a pressure of about 4.5 GPa by Raman spectroscopy [8], and the PdF 2 -type structure has been predicted to be stable as a highpressure phase at a pressure higher than 6.5 GPa by theoretical calculation [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that a phase transition from the rutile- type to the CaCl 2 -type structure occurs at a pressure of about 4.5 GPa by Raman spectroscopy [8], and the PdF 2 -type structure has been predicted to be stable as a highpressure phase at a pressure higher than 6.5 GPa by theoretical calculation [9]. Whereas the bulk properties of high surface area materials are well investigated, it is important to investigate the surface structure of such materials.…”
Section: Introductionmentioning
confidence: 99%